Prevalence and severity of anemia in pediatric hemodialysis patients. - Azhir, Afshin; Nasiri, Jafar; Gheisari, Alaleh (Saudi Medical Journal, 2007)
OBJECTIVES: To determine the prevalence and severity of anemia, and to identify independent predictors for anemia in children on hemodialysis.METHODS: We conducted this cross sectional study on 25 children aged 7-20 years receiving hemodialysis from September 2005 to January 2006 in Isfahan University of Medical Sciences, Isfahan, Iran.RESULTS: A total of 22 (82%) patients had hemoglobin (Hb) level of <11 g/dL (anemia) and 12 (48%) patients had Hb values <8 g/dL (severe anemia). The mean age was 15.5 ± 3.7 years. Mean time on hemodialysis was 20.44 ± 15.25 months. Anemia was more common and severe among children who were on dialysis <6 months. There was an inverse relation between severity of anemia and duration of hemodialysis (r=-0.465, p=0.019). Nearly all patients were treated with recombinant human erythropoietin (rHuEPO). Children with severe anemia received a slightly higher dose of erythropoietin (r=0.202 p=0.09). There was a correlation between serum albumin and Hb level (r=0.511, p=0.01). Intact parathyroid hormone (iPTH) levels were >200 pg/mL in 16 patients (66%) and >400 pg/mL in 9 patients (37.5%). There was a reverse correlation between iPTH level >200 pg/mL and Hb level (r=-0.505, p=0.046).CONCLUSIONS: The prevalence of anemia in our study appears to be higher than that reported in the other studies in spite of extensive use of rHuEPO and iron supplementation. We found this to be especially true for patients who were on dialysis <6 months and with low albumin and severe hyperparathyroidism.